File Sharing System Using Samba For Mathematics Laboratory - Dian Tri Wiyanti; David Mubarok; Muhammad Zuhair Zahid (Jurusan Teknologi Informasi Universitas Semarang, 2018)
In the computer laboratory of Mathematics Department previously installed in the network of Novell Netware 5 operating system. But file sharing problem is when client upgrades the operating system. The server can not be accessed from the client. So finally the data management was decided not to go through the server. Another constraint is not being able to update regularly, so it certainly will be vulnerable to viruses. Within 1 month required to re-install twice because of virus attacks, malware, and others. The idea is to build a network which is server-based integrated, and make improvements on the server side system more effective and efficient, and safe from hackers or viruses. This research also contributes to the realization of green computing that supports the commitment of college conservation.